PETRE FRANGOPOL – A FIGHTER IN THE PUBLIC ARENA - BANABIC, Dorel (Studia Universitatis Babeș-Bolyai Chemia, 2021)
I met Professor Frangopol through his articles published in the first part of the 2000s in the Aldine supplement of the newspaper România Libera. Subsequently, we collaborated in various committees and, lately, in organizing symposia on education and research. I had the pleasure to collaborate with Professor Frangopol on the editing of a volume entitled “Romanian education and research. The present state and perspectives” which brings together the works presented in a workshop of the same name organized by the University of Bucharest in 2017. One of his most well-known public activities is the publication of a series of volumes entitled “Mediocrity and Excellence: a radiography of science and education in Romania.” Like clockwork (every three years), from 2002 to 2019 (7 volumes), Professor Petre Frangopol compiled the articles he published in newspapers and specialized journals on the situation in Romanian education and research.